Faktor Dominasi Pengembangan Karir terhadap Komitmen Organisasi - Yoga Satria Widjaya; Ratna Indrawati; Cri Sajjana Prajna Wekadigunawan (Jurnal Manajemen Kesehatan Indonesia, 2021)
Low commitment from employees to the hospital could be seen from the low number of employees who remain working. Compensation did not match expectations and the work climate was uncomfortabel and the lack of training as one of the career development processes made the low commitment of employees to the hospital. This study aims to provide empirical evidence of the effect of compensation and work climate on organizational commitment mediated by career development. The research method used will be quantitative methods with the type of causality research. Data source will be primary. Subjects to be analyzed will be all employees except the doctors in X hospital Cisauk Tangerang. Analysis will be using structural path analysis. Results of this study were compensation, work climate, and career development simultaneously have a positive and significant effect on organizational commitment. Partially, compensation and work climate had a positive and significant effect on career development. The research findings were the direct effect of compensation and work climate on organizational commitment greater than mediated by career development. The effect of career development is greater on organizational commitment compared to compensation and work climate.